Analisis Faktor-Faktor yang mempengaruhi Skala Ekonomi dalam Industri Mikro Kecil di Indonesia - Anna, Yuni (Strata Social and Humanities Studies, 2024)
This study investigates the factors influencing economies of scale in Indonesian micro and small industries (MSIs), focusing on labor, capital, and technology. Recognizing the critical role of MSIs as the backbone of the Indonesian economy, this research examines how these key production factors impact MSI income, ultimately reflecting their economic scale. A quantitative approach was employed using secondary data from the Central Statistics Agency (CSA) and scientific journals. The sample comprised micro and small industries across all 34 Indonesian provinces, categorized by employee count. Data analysis involved classical assumption tests, multiple linear regression, and hypothesis testing to evaluate the relationship between variables and their influence on MSI income. The findings reveal that the number of workers or labor, capital, and technology positively and significantly affect MSI income partially and simultaneously. An increase in workers directly impacts income due to enhanced productivity. This study recommends improving workforce quality through training, facilitating capital access via innovative financing schemes, and encouraging technology adoption through targeted programs. Future research should explore additional factors influencing the MSI economic scale to inform comprehensive policy development.